Factors influencing the choice in Incoterms among Malaysian manufacturers - Yaakub, Sabariah; Leong, Ying Szu (2017)
The International Commercial Terms (Incoterms), introduced and governed by International Chamber of Commerce (ICC) are standard trade terms used in international and domestic sales contract. The latest version, INCOTERMS 2010 states the obligations and responsibilities of importers and exporters regarding transport costs and risks as well as the responsibilities for insurance and customs formalities.This paper seeks to find out the most frequently used Incoterms and examine the factors that influences the choice of Incoterms among Malaysian manufacturers. Data was collected using survey methods and then analysed using univariate (descriptive) analysis. A total of 335 questionnaires were distributed to manufacturers in Malaysia using a sampling framework from the Federation of Malaysian Manufacturers (FMM). Of the 335 questionnaires distributed, 60 were returned yielding a response rate of 17.9%. Findings indicate that FOB (Free On Board) were the most frequently used Incoterms and that the factors that influence choice of Incoterms can be divided into two types: external environments and internal factors. Among the external environment, the strongest influence are freight issue, transport issue and tariff classification. For the internal environment, the strongest influence comes from mode of transportation, habits and practices of the organization and experience of the company.The main contribution of this study is towards narrowing the gap in knowledge regarding Incoterms as past research indicated that it is still relatively unknown and should highlight Incoterms selection, among others.